The candidate's dilemma anticorruptionism and money politics in Indonesian election campaigns - Kramer, Elisabeth, 1981- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2022)
"This book considers the 'puzzle' of how those vying for a seat in Indonesia's national legislature make decisions about their campaigns, telling this story through the eyes of three self-identified anticorruption candidates. It explores how these candidates navigate the pressure to engage in money politics and vote-buying while electioneering"--